(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In this article author conducted a comparative analysis: common and specific in state administration in the epoch of T Usubalievand presently.